Contextualising the dead – Combining geoarchaeology and osteo-anthropology in a new multi-focus approach in bone histotaphonomy. (October 2018) - Brönnimann, David; Portmann, Cordula; Pichler, Sandra L.; Booth, Thomas J.; Röder, Brigitte; Vach, Werner; Schibler, Jörg; Rentzel, Philippe
Abstract: Histotaphonomy has become an important area of research in funerary archaeology. It focuses on diagenetic alterations in bone microstructure and the reconstruction of post-mortem processes. Microbial bioerosion is the most common diagenetic change observed in archaeological bone, and its probable causes have been the subject of ongoing discussions. This paper presents a new integrative approach that combines methods from physical anthropology and geoarchaeology. The aim is to contextualise samples in regard to their sedimentary milieu (sediment type), the sedimentation processes they underwent, and the specific archaeological features they originate from. The analysis is based on 208 human and animal skeletal fragments from the Late La Tène site of Basel-Gasfabrik recovered from various feature types and embedded in different sediments. Both 80 μm and 30 μm thin sections were graded semi-quantitatively on a scale of 0 or 1 to 5 in regard to bacterial attack (BAI), Wedl tunnels (WTI), cyanobacterial attack (CAI), the formation of cracks (CRI), the collagen content (COI), and thermal alterations (HEI). Our results evinced no correlations between the intensity of bacterial attack and sediment types or sedimentation processes respectively. We therefore deduce that bacterial degradation of bone is mainly caused by endogenous gut bacteria. Wedl tunnels, on the other hand, are chiefly found in bones from exposed surfaces. Bone collagen content, as measured by birefringence, is dependent on a variety of factors, with thermal alteration being among the most important. Unlike the 80 μm sections used in anthropological investigations, the 30 μm thin sections typically utilized in geoarchaeological analyses permitted a reliable distinction of microbial bioerosion types. Our context-oriented histotaphonomic approach allows detailed conclusions on the causes of microbial bioerosion in bone. Moreover, it provides an important tool for reconstructing the post-mortem biographies of human and animal remains, especially in regard to (multi-stage) mortuary practices and the analysis of sedimentation processes. Thus, this novel approach generates a wealth of information from individual skeletal elements as well as from bone fragments embedded in soil samples.